DIGITAL FREEDOM OF EXPRESSION: COMPARATIVE LEGAL MODELS IN INDONESIA, CHINA, AND UNITED STATES OF AMERICA - Andes Robensyah (Universitas Syiah Kuala, 2026)
The rapid evolution of digital technology has made freedom of expression a critical transnational issue, yet a legal gap exists in how national implementations diverge from uniform international standards like the International Convention on Civil and Political Rights (ICCPR). Previous research often lacks a cross-border perspective, leaving a void in understanding how contrasting political philosophies impact digital rights. This study addresses the question of how digital expression is governed under three distinct legal ideologies: the constitutional democratic, digital authoritarian, and constitutional liberal models.Using comparative legal research methods, the study analyzes the legal frameworks, norms, and practices of Indonesia, China, and the United States of America (USA). Key findings reveal that Indonesia employs a mixed model; while the 1945 Constitution guarantees rights, the ITE Law has historically caused a